Effects of comprehensive education protocol in decreasing pre-hospital stroke delay among Chinese urban community population. (1st June 2013) - Chen, Shengyun; Sun, Haixin; Zhao, Xingquan; Fu, Paul; Yan, Wang; Yilong, Wang; Hongyan, Jia; Yan, Zhang; Wenzhi, Wang
Abstract : Background and purpose: Studies have shown that awareness of early stroke symptoms and the use of ambulances are two important factors in decreasing pre-hospital stroke delay. The purpose of this study is to evaluate a comprehensive educational stroke protocol in improving stroke response times. Method: Two urban communities in Beijing (population ≍50 000), matched in economic status and geography, were enrolled in this study. A comprehensive educational protocol, which included public lectures and distribution of instructive material for the community and its medical staff, was implemented from August 2008 to December 2010. Surveillance of new onset stroke in both communities was carried out during the same period. Pre-hospital delay time and percentage of patients using emergency medical services (EMS) were compared between the two communities. Results: After comprehensive educational protocol, we found that: (i) pre-hospital delay (time from stroke symptom onset to hospital arrival) decreased from 180 to 79 minutes, (ii) the proportion of patients arriving within three hours of stroke onset increased from 55·8% to 80·4%, (iii) pre-hospital delay of stroke patients with symptoms of paralysis, numbness, and speech impediments was decreased, and (iv) the proportion of stroke patients calling for EMS increased from 50·4% to 60·7%. Conclusion: The comprehensive educational stroke protocol was significantly effective in decreasing pre-hospital stroke delay.